Unlocking Amil performance: Leadership, knowledge management capability, and organizational culture - Asya’bani, Nispia; Rusgianto, Sulistya; Ratnasari, Ririn Tri; Ryandono, Muhammad Nafik Hadi; Susanto, Arva Athallah (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study examines the impact of Islamic leadership style and Knowledge Management Capability (KMC) on improving amil performance in Indonesia, with organizational culture serving as a mediating variable. In addition, this study identified potential future research directions in this field.Methodology – This research employs a quantitative approach utilizing Structural Equation Model (SEM) analysis with Smart-PLS 4 software. The sample was selected through purposive sampling, targeting 130 amils in Indonesia. Findings – The findings reveal that both Islamic leadership and Knowledge Management Capability (KMC) have a significant positive influence on amil performance, both directly and through the mediating role of organizational culture. Furthermore, Islamic leadership directly enhances knowledge-management capabilities. Implications – This study provides valuable insights into the application of knowledge management practices and the role of Islamic leadership in enhancing the performance of amil zakat (zakat institutions). This study's implications highlight the need for greater focus on improving amil performance to maximize the efficiency of zakat collection and management.Originality – To the best of our knowledge, this analysis represents actionable recommendations for improving the efficiency of zakat collection and distribution through enhanced amil performance with the combination of KMC and organizational culture, which has rarely been studied in zakat institutions.